SOLVABILITY RATIO ANALYSIS TO ASSESS THE FINANCIAL PERFORMANCE OF PT KARYA TANTRI ABADI - Bagus Priyangga; Ibnu Farid; Jena Sarita; Siti Fatimah (OIKONOMIA: Journal of Economics and Management Science, 2024)
The aim of this research is to use the solvency ratio to test the financial performance of PT Karya Tantri Abadi. Descriptive research using a qualitative approach is the type of research used in this research. Based on research results, the financial performance of PT Karya Tantri Abadi during the period 2020 to 2022 illustrates extraordinary achievements in terms of profitability, efficient use of assets and debt management. The research results show that PT Karya Tantri Abadi has a fairly good level of solvency with relatively low DAR and DER values compared to industry standards. The company shows a tendency to increase the use of debt in its operations in 2021, but has taken steps to reduce its debt or increase its equity in 2022. In conclusion, PT Karya Tantri Abadi has good solvency and is able to meet its long-term obligations. However, companies need to continue to monitor and manage their debt carefully to maintain optimal levels of solvency.